Fair Law in Money Laundering with the Origin of Corruption with the Concept of Asset Seizure - Sitompul, Ariman; Aisyah, Aisyah (International Asia Of Law and Money Laundering, 2024)
Money laundering is a guarantee to get the results of criminal acts establish the economic responsibilities of a country and especially of tact currency exchange rates will be more difficult. Glassy from this, the achievement of assets becomes important because the method of approach used to be known as